In silico screening of cancer-associated mutations in the HSA domain of BRG1 and its role in affecting the Arp-HSA sub-complex of SWI/SNF. (December 2018) - S., Alagu Sankareswaran; Goutham R.N., Arun; Mohan S., Suma
Graphical abstract: Highlights: Proposed the structure of human Arp-HSA complex consists of β-actin, BAF53A and HSA domain of BRG1. Seven deleterious cancer-associated mutations in the HSA domain of BRG1 has been identified. Six deleterious HSA domain mutations, R466H, R469W, Y489C, K502N, R513Q, and R521P, were subjected to MD simulation studies. Distinct structural effect of mutations observed in destabilizing the Arp-HSA complex. Abstract: SWI/SNF (SWItch/Sucrose Non-Fermentable) complexes regulate the gene expression programs by remodeling the nucleosome architecture of the chromatin functional elements. These large multi-component complexes comprise eight or more subunits and are conserved from yeast to human. Noticeably, nuclear actin and actin-related proteins (Arps) are an integral part of these complexes and are known to directly interact with the helicase-SANT-associated (HSA) domain of ATPase subunit. Recently, SWI/SNF subunits are gaining importance because of the prevalence of cancer-causing mutations associated with them. The functional characterization of the mutations in the SWI/SNF subunits is important for understanding their role in tumorigenesis and identifying potential therapeutic strategies. To study the actin-related complex of human SWI/SNF and the cancer-associated mutations interfering Arp assembly with the ATPase subunit, we modelled the structure of the β-actin-BAF53A-HSA complex based on the yeast Arp-HSA complex (PDB ID: 4I6M). Seven deleterious mutations in the HSA domain of BRG1 were identified based on the functional screening of cancer-associated mutations in the COSMIC database. Detailed structural analysis of the six mutations (R466H, R469W, Y489C, K502N, R513Q and R521P) based on molecular dynamics (MD) simulations reveal the distinct effect of each mutation in destabilizing the structure of the Arp-HSA complex. Predominantly we could notice the long-range effect of the HSA mutations in influencing the dynamics of the Arp subunits.